2021
DOI: 10.1186/s12936-021-03896-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Plasmodium falciparum infection in pregnant women in Burkina Faso: a community-based cross-sectional survey

Abstract: Background Malaria in pregnancy remains a public health problem in sub-Saharan Africa. Identifying risk factors for malaria in pregnancy could assist in developing interventions to reduce the risk of malaria in Burkina Faso and other countries in the region. Methods Two cross-sectional surveys were carried out to measure Plasmodium falciparum infection using microscopy in pregnant women in Saponé Health District, central Burkina Faso. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(55 reference statements)
2
2
0
Order By: Relevance
“…The prevalence of microscopy-detected malaria in our study was similar to that reported at predelivery in the same area, with a prevalence of 17.5% (95% CI 14.6–20.8%). A similar trend was reported in the central region of the country (a similar malaria transmission setting), with a prevalence of microscopy-detected P. falciparum infection of 15.7% (95% CI 12.3–20.2%) during the second and third trimesters of pregnancy [ 7 ]. This shows that malaria transmission intensity in the country is consistent throughout the pregnancy [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of microscopy-detected malaria in our study was similar to that reported at predelivery in the same area, with a prevalence of 17.5% (95% CI 14.6–20.8%). A similar trend was reported in the central region of the country (a similar malaria transmission setting), with a prevalence of microscopy-detected P. falciparum infection of 15.7% (95% CI 12.3–20.2%) during the second and third trimesters of pregnancy [ 7 ]. This shows that malaria transmission intensity in the country is consistent throughout the pregnancy [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 73%
“…In Burkina Faso, the epidemiology of malaria has been comprehensively described for different age groups and conditions [ 7 11 ], and various interventions have been implemented to improve health care [ 12 – 14 ]. However, data on the characteristics of malaria in pregnancy are sparse, particularly in rural areas, and it is an obstacle for adequate control strategies planning and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with reports of several studies, malaria parasite levels decreased with increasing maternal age and gravidity status [ 1 , 3 , 49 , 52 ]. This might be linked to pregnancy-associated anti-parasite immunity.…”
Section: Discussionsupporting
confidence: 92%
“…In Burkina Faso, the study was conducted in the Centre-West of the country, in the Nanoro Health District, catchment area (about 145,000 inhabitants), where malaria transmission is high and extremely seasonal (June-December). Studies in Burkina Faso have estimated prevalence of malaria infection amongst pregnant women at between 15.7% and 18.1% [ 31 , 32 ]. In Burkina Faso, at the time of the trial, pregnant women were expected to pay for malaria treatment.…”
Section: Methodsmentioning
confidence: 99%